The impact of motivational and cognitive involvement on EFL learners' task performance. Issue 2 (30th June 2016) - Hasannejad, Mohammad Reza; Zoghi, Masoud; Davatgari Asl, Hanieh
Abstract: Although the role of task factors which can influence learners' affective characteristics such as motivation and cognition has been of researchers' enduring interest, few empirical studies have investigated motivational and cognitive operational impacts on task performance in instructional settings. This study investigated the independent and combined effects of motivational and cognitive pre-task strategies on listening-task performance by intermediate learners of English at a private language institute in Guilan. After homogenising the proficiency level of learners, three experimental groups and one control group were nominated to contribute to the study. In each treatment session, the motivation, cognitive, motivation and cognitive, and control groups engaged in the pre-treatment listening tasks and took the post-treatment tasks following brief motivationally (EX1), strategically (EX2), and motivationally and strategically (EX3) instructions, while the control group did not undergo any special kind of treatment. The results from paired samples t -test suggested that motivational, cognitive, or motivation and cognitive strategy instruction helped all experimental groups improve all their five post-treatment task performance. Although the results indicated that motivational and cognitive pre-task strategies could be a substitute for each other, it was shown that the combined support and promotion of them could induce better results.